Manejo da adubação orgânica visando agroecossistemas sustentáveis de café conilon no Estado do Espírito Santo - Silva, Victor Maurício da (2012)
The conilon coffee plant (Coffea canephora Pierre ex Froehner) has high nutrient requirement and the soil recovery is usually done thru mineral fertilizers. To reduce them, the use of organic waste available on the farm can be an alternative. The objectiv